Correlation analysis of lymphocyte surface antigen and THBS1 levels with myocardial injury in sepsis patients: THBS1 levels in sepsis with myocardial injury - Wei, Min; Wang, Wuchao; Wang, Dongxiao; Cheng, Yifei; Liu, Xiaoyu; Xiu, Limei (Journal of Medical Biochemistry, 2026)
Objective To analyze the relationships among the surface antigens of lymphocytes in patients with sepsis, the level of thrombospondin-1 (THBS1), and myocardial injury. Methods 360 sepsis patients who were hospitalized to our hospital between January 2023 and January 2025 were chosen. 170 patients with myocardial injury and 190 patients without myocardial injury were selected from the patient group based on whether or not they had myocardial injury. Serum THBS1 levels, immune function (CD4+, CD8+, and CD4+/CD8+), myocardial injury markers (creatine kinase MB (CK-MB), heart-type fatty acid binding protein (H-FABP), N-terminal pro-B-type natriuretic peptide (NT-proBNP), and cardiac troponin I (cTnI)), and echocardiographic markers (left ventricular ejection fraction (LVEF), early diastolic velocity to atrial contraction velocity ratio (E/A), and cardiac output (CO)) were compared. Correlations between immune function, THBS1 levels, myocardial injury indicators, and echocardiographic markers in individuals with myocardial damage and infection were examined. To predict sepsis with myocardial infarction, the serum THBS1 value was evaluated using the receiver operating characteristic (ROC) curve and the area under the curve (AUC). Results While the myocardial injury group had significantly lower levels of CD8+ T cells in peripheral blood, LVEF, E/A, and CO, the nonmyocardial injury group had significantly higher levels of CD4+, CD4+/CD8+, serum THBS1, CK-MB, H-FABP, NT-proBNP, and cTnI (P<0.05). Patients with sepsis and myocardial injury had considerably higher peripheral blood CD8+ T cell counts with LVEF, E/A, and CO (P<0.05) and significantly lower counts with CK-MB, H-FABP, NT-proBNP, and cTnI (P<0.05). CK-MB, H-FABP, NT-proBNP, and cTnI were strongly positively correlated (P<0.05) with peripheral blood CD4+ and CD4+/CD8+ T cell counts, while LVEF, E/A, and CO were significantly correlated negatively (P<0.05). Serum THBS1 levels had a substantial negative correlation (P<0.05) with LVEF, E/A, and CO and a strong positive correlation (P<0.05) with CK-MB, H-FABP, NT-proBNP, and cTnI. With a sensitivity of 80.03% and specificity of 87.43%, the serum THBS1 concentration demonstrated an AUC of 0.892 (95% CI: 0.857–0.947) for predicting both sepsis and myocardial damage. Conclusion Sepsis patients’ levels of THBS1 and lymphocyte surface antigens are somewhat linked to myocardial damage, and THBS1 is anticipated to function as a biomarker for anticipating myocardial damage in sepsis patients.